CROWDFUNDING ANALYSIS: EXPLORING THE FACTORS IN DOTA 2 INTERNATIONAL BATTLE PASS PURCHASES - Soloty, Edmund; Worang, Frederik G.; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2024)
Abstract: Dota 2 The International Championship’s prize pool has been fully crowdfunded by the community itself since The International Championship 2013 via the battle pass system; where customers may purchase the battle pass for US9.99 to gain access to tournament and event features and a large range of earnable cosmetic goods, which then 25% of the battle pass earnings went into The International’s prize pool. Using the Exploratory Factor Analysis on 20 different variables on Crowdfunding, 2 factors emerge: “Brand Appeal” consists of: Customer Engagement, Brand Image, Product Quality, Impulsive Consumption, Perceive Ease of Use, Pricing, Customer Trust, Product Variety, Differentiation Strategy, Hedonic Motivation, Conspicuous Consumption, Performance Expectancy, Customer Experience, Perceived Value, Social Influence, Habitual Consumption, and Customer Loyalty. And the second factor called “Consumer Influence Composite” consisting of: Addictive Consumption, Perceived Risk, and Promotion. Keyword: Crowdfunding, Dota 2, The International Championship, Battle Pass, Customer Engagement, Brand Image, Product Quality, Impulsive Consumption, Perceive Ease of Use, Pricing, Customer Trust, Product Variety, Differentiation Strategy, Hedonic Motivation, Conspicuous Consumption, Performance Expectancy, Customer Experience, Perceived Value, Social Influence, Habitual Consumption, Customer Loyalty, Addictive Consumption, Perceived Risk, Promotion.